Screens to see the world. Television stereotypes of the mexican indigenous population and the generation of prejudice - Muñiz, Carlos; Saldierna, Alma Rosa; Marañón Lazcano, Felipe de Jesús; Rodríguez, Alba Belinda (2013)
Abstract Introduction. Stereotypes are socially-structured beliefs about a particular social group, which can be derived from direct or indirect contact with members of that group. In this regard, it has been pointed out that media representations can generate and reinforce stereotypes that lead to the development of more or less prejudiced attitudes. Objectives. This study seeks to examine whether this process occurs with respect to the Mexican indigenous population, in the context of the metropolitan area of Monterrey. Methods. The study combined two methods: the first one consisted of the content analysis of fiction TV programmes in order to identify possible stereotypes about Mexico’s indigenous population; the second instrument was a survey applied to high school students of the metropolitan area of Monterrey in order to investigate the relationship between their beliefs and prejudiced attitudes towards indigenous people. Conclusions. Results confirmed the impact of the consumption of media stereotypes on the level of prejudice towards indigenous people, but not on the stereotyping of this sector of the population.